Analisis Faktor Risiko Kejadian Malaria pada Anak (Usia 0-18 Tahun) di Kabupaten Purworejo - Ningtyas, Rahayu; Martini, Martini; Wurjanto, Moh. Arie; Hestiningsih, Retno (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
API in Indonesia increased from 0,9/1000 people in 2019 and 2020 to 1,1/1000 people in 2021. One of the districts in Central Java with the highest malaria cases in 2022 is Purworejo, with 544 cases and 141 cases among them occurred in children 0-18 years. This study aims to analyze risk factors of malaria in children aged 0-18 years in Purworejo Districts. This study use case-control design with ratio 1:1 in Bener, Kaligesing, and Purworejo Sub-district during February-June 2023 to parents/ guardians from children aged 0-18 years. Data were processed use SPSS and analyzed univariately and bivariately use Chi Square test in cross table. Analysis results show that malaria incidence in children 0-18 years in Purworejo are influenced by the knowledge of parents/ guardians (p = 0,001; OR = 2,901; 95% CI = 1,507 – 5,585) and malaria prevention practice by parents/ guardians (p = 0,035; OR = 1,993; 95% CI = 1,040 – 4,208). Malaria incidence in children was not influenced by the attitude of parents/ guardians (p = 0,159). Child’s age (p = 0,020; OR; 0,341; 0,154-0,751) and child’s education (p = 0,039; OR = 0,415; 95% CI = 0,190 - 0,903) are a protective factors of malaria incidence in children. Malaria incidence in children aged 0-18 years in Purworejo are influenced by parental/ guardian behavior and environmental factors, age and educational characteristics of children can protect children from malaria.